Young People and the Psychological Orientation towards Politics (POTP): Identifying Gender, Ethnicity, and Educational Background as Predictors - Adinugroho, Indro; Wibawa, Dhevy Setya (Bina Nusantara University, 2021)
The research addressed a psychological orientation of young people towards politics (Psychological Orientation towards Politics/POTP). It focused on three primary variables: Political Efficacy (PE), Political Interest (PI), and Political Knowledge (PK) in relation to gender identity (male and female), ethnicity (Tionghoa & non-Tionghoa), and educational background (socio-political science and non-socio-political science). As a young democratic country, Indonesia faced various challenges while pursuing robust democracy like another developed country. One big challenge faced by Indonesia was related to the awareness of political participation, the most central element for a democratic country where people must be aware that they have legitimate power. To overcome these challenges, investigation on variables related to psychological dimensions of humans was needed to start developing a behavioral map of political behavior in Indonesia, particularly concentrating on young people as the next generation of Indonesia democracy. Data were collected from the online panel. Results from descriptive statistics and linear regression models with three blocks have shown that these three variables have played an important role in determining POTP in young people. PK is the most affected variable compared to the other two variables. In conclusion, the identification of ethnicity (Tionghoa vs. non-Tionghoa) and educational background are possible factors that may affect the degree of POTP in the female group.